Analysis of the Impact of Compensation and Workload on the Job Satisfaction Level of Shoe Factory Employees - Furi Candra Diana Putri; Irbayuni, Sulastri (Jurnal Ilmiah Sumber Daya Manusia, 2024)
This study aims to analyze the effect of compensation and workload on CV Samodera Shoe Factory’s employee job satisfaction. This research uses quantitative methods using Proportionate Random Sampling technique as many as 67 production employees. Data collection through questionnaires distributed to production employees. The variables used in this study are: independent variables, namely Compensation (X1), Workload (X2), and the dependent variable is Job Satisfaction (Y). The anaylitical tool used in this study is the Partial Least Square (PLS) model to construct a model that can be assumed when there are several factors. The findings indicate that compensation contributes to job satisfaction, but not very strongly, while workload has a strong contribution to job satisfaction.